Franklian treatment with Vietnam veteran couples - Lantz, James E. (Journal of religion and health, 1991)
In this article, the Franklian treatment method of existential reflection is described as it can be used in marital therapy with Vietnam veterans. The author also provides information about treatment results with twenty-three Vietnam veteran couples from 1974 to 1987.